Brain morphological changes in acquired hearing loss: A surface-based morphometry study - Hye Ah Joo; Hwon Heo; Tae Uk Cheon; Yun Ji Lee; Yeonjoo Choi; Woo Hyun Shim; Hong Ju Park (PLoS ONE, 2026)
Prolonged auditory deprivation induces neuroplastic changes throughout the brain, including the auditory system. Understanding these structural alterations is crucial for optimizing auditory rehabilitation strategies. This study investigated brain morphological alterations associated with bilateral severe-to-profound sensorineural hearing loss (bilateral deafness; BD), focusing on cortical thickness (CT) and cortical volume (CV), and examined whether alterations in auditory-related cortical regions were associated with the duration of deafness (DoD) or hearing aid use (DoHA). High-resolution three-dimensional T1-weighted MRI data from 47 BD patients (≥10 years of hearing loss) and 73 normal hearing (NH) controls were retrospectively analyzed using surface-based morphometry (SBM) in FreeSurfer. Vertex-wise group comparisons of CT and CV were performed using a general linear model controlling for age. Partial correlation analyses were then conducted between CT/CV of eight auditory-related regions of interest and DoD/DoHA. Compared with the NH group, the BD group showed reduced CT in the bilateral superior temporal gyri and lateral occipital cortices, along with significant CV reductions in the bilateral superior temporal gyri, superior parietal cortices, and lateral occipital cortices. Notably, longer DoHA was positively correlated only with CT in the right superior temporal gyrus (r = 0.409, p = 0.005, FDR-adjusted p = 0.040). These findings demonstrate that long-term BD is associated with widespread cortical atrophy, affecting regions involved in auditory processing and the integration of somatosensory and visual information. Sustained hearing aid use may help preserve cortical structure, suggesting that timely auditory rehabilitation could slow neurodegeneration and potentially mitigate cognitive risks associated with hearing loss.